A Bivalent Activatable Fluorescent Probe for Screening and Intravital Imaging of Chemotherapy‐Induced Cancer Cell Death. Issue 5 (16th December 2021) - Barth, Nicole D.; Mendive‐Tapia, Lorena; Subiros‐Funosas, Ramon; Ghashghaei, Ouldouz; Lavilla, Rodolfo; Maiorino, Laura; He, Xue‐Yan; Dransfield, Ian; Egeblad, Mikala; Vendrell, Marc
Abstract: The detection and quantification of apoptotic cells is a key process in cancer research, particularly during the screening of anticancer therapeutics and in mechanistic studies using preclinical models. Intravital optical imaging enables high‐resolution visualisation of cellular events in live organisms; however, there are few fluorescent probes that can reliably provide functional readouts in situ without interference from tissue autofluorescence. We report the design and optimisation of the fluorogenic probe Apotracker Red for real‐time detection of cancer cell death. The strong fluorogenic behaviour, high selectivity, and excellent stability of Apotracker Red make it a reliable optical reporter for the characterisation of the effects of anticancer drugs in cells in vitro and for direct imaging of chemotherapy‐induced apoptosis in vivo in mouse models of breast cancer. Abstract : We describe Apotracker Red as a single fluorescent activatable probe for robust quantification of cancer cell death in fluorescence‐based assays and in vivo using multiphoton intravital imaging in mouse models of breast cancer.